Public health costs for selected cities in the state of Paraná: A polygonal model adjustment analysis - Marcelo Ortega Massambani; Sidnei Pereira do Nascimento; Marcia Regina Gabardo da Camara; Sarah Silveira Diniz (Economia & Região, 2013)
The aim of the article is to analyze public health expenditures and the health quality indicator of the municipalities of Londrina, Curitiba, Maringá and Foz do Iguacu located in state of Paraná in the period 2000-2011. The hypothesis is that the law “Health Pact” impacted positively in the selected municipalities, before and after 2006. This study uses polygonal methodology for the health sector of selected cities in Paraná to identify regional differences of the impacts of legislation related to public health expenditures and the health quality indicators. The results showed that there were positive effects in public health spending per capita in the period and improvements in the health quality indicators. The results of the adjustments polygonal model showed that after the implementation of the "Health Pact", Londrina increased the share of public health expenditure, compared to cities of Curitiba, Maringá and Foz do Iguaçu.